ANALISIS PENILAIAN DAN PENCATATAN PERSEDIAAN BERDASARKAN PSAK 14 PADA PT. PENGUIN INDONESIA CABANG MEDAN - Rizky Ade Syahputra; Ardhansyah Putra (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2023)
Penguin Indonesia Branch Medan is one of the companies located in the Medan Star Tanjung Morawa Industrial Area, Deli Serdang Regency. This study discusses the Valuation and Recording of Inventory based on PSAK 14 at PT. Penguin Indonesian Branch Medan. Inventories are assets for sale in the normal business activities of a trading company, in the production process for sale, in the form of materials or supplies (supplies) for use in the production process or providing services. Valuation and recording of merchandise inventory is an important indicator of inventory. This research is a descriptive research with a qualitative approach. The purpose of this study was to find out whether the inventory valuation and recording at PT. Penguin Indonesian Branch Medan complies with PSAK No.14. The type of data used is primary data in the form of interview results and secondary data in the form of documentation data and company archives for February 2023. Then the data that has been collected from the company is then analyzed using a descriptive method by collecting data, processing and analyzing the data so that an overview is obtained. the problem under study. The results showed that basically the method of valuation and inventory recording at PT. Penguin Indonesian Branch Medan complies with PSAK No. 14. By applying the perpetual method in the process of recording merchandise inventory. Meanwhile, to assess the merchandise inventory of PT. Penguin Indonesia Branch Medan applies the FIFO first in first out (MPKP) method.